Incentivizing Sustainable Private Sector Investment in Timber Plantations in Myanmar : Policy Options to Encourage Socially and Environmentally Responsible Investment - World Bank (World Bank, Washington, DC, 2020)
Forestry has traditionally been one of Myanmar’s most important economic sectors, generating more in export earnings in the period 2010-2018. It is estimated that the country will have lost 12 million ha of forest between 1990 and 2020 - the third largest absolute forest loss of all countries during that period. The government now aims to restore or reforest about 884,000 ha on reserved forest (RF) and public protected forest (PPF) land under its 2016-28 Myanmar reforestation and rehabilitation program (MRRP). A range of reforms is needed to encourage private sector investment. These include: (i) identification of sufficiently large areas of suitable land close to potential processing sites or transport infrastructure and planning of land-use allocation; (ii) improving the availability of information on identified areas and on the process of acquiring plantation leases; (iii) streamlining leasing procedures and terms and scope of leases, including possible private management of state plantations; (iv) simplifying regulations on harvest and transport of plantation timber; (v) reviewing the suitability of current fiscal incentives, including tax holidays; (vi) improving information on areas and productivity of established plantations; and (vii) identifying priority research and development needs and delivery mechanisms.